Association of the interleukin-10 (IL-10) gene polymorphisms with ovarian cancer risk: a systematic review and meta-analysis - Totou, Stavri; Kalali, Datis (Journal of Medical Science, 2023)
Background. Ovarian cancer is a cancer with high fatality due to its symptomless nature, which leads to a late diagnosis. Therefore, there is an urgent need to discover genetic markers related to predisposition to the disease. With anti-inflammatory cytokines playing a major role in cancer predisposition, the present systematic review and meta-analysis were undertaken to evaluate the association of the interleukin-10 (IL-10) gene polymorphisms with ovarian cancer risk.Material and methods. Online databases were searched for articles dating from June 2023 until inception for studies assessing the frequencies of IL-10 polymorphisms in ovarian cancer patients and controls. The odds ratios of the genotypes, alongside their respective 95% confidence intervals, were calculated under three different genetic models.Results. A total of 5 records studying the IL-10-819 C>T and IL-10-1082 G>A polymorphisms were included in the quantitative analysis. The meta-analysis suggested that the IL-10-819 C>T polymorphism was significantly associated with the risk of ovarian cancer under a dominant (CT + TT vs CC) inheritance model (OR = 2.67; 95% CI = [1.17,6.12]; p = 0.02).Conclusions. The meta-analysis suggested that the T allele of the IL-10-819 C>T is associated with an increased risk of ovarian cancer. However, no statistically significant association exists between the IL-10-1082 G>A polymorphism and ovarian cancer. Future studies are required to verify these results further.
Keywords: Ovarian cancer; interleukin-10; IL-10; polymorphisms; genetic predisposition